KATA SERAPAN BAHASA ARAB DALAM BAHASA JAWA BIDANG AGAMA PADA KAMUS BAOESASTRA KARYA W.J.S POERWADARMINTA - Tri Windarti; Retno Purnama Irawati; Muchlisin Nawawi (Universitas Negeri Semarang, 2023)
The community uses Arabic absorption vocabulary in Javanese, which has a different meaning from the original word, especially in the field of religion. Analysis of Arabic absorption words that have changed meaning, especially in the field of religion, in the Baoesastra Dictionary by W.J.S Poerwadar Minta is the focus of the problem in this article. The problems studied in this article are (1) the types of Arabic vocabulary absorption in the field of religion which are absorbed into Javanese, (2) changes in the meaning of Arabic vocabulary in the field of religion which are absorbed into Javanese, and (3) changes in the types of Arabic absorption words into Javanese in the field of religion. This qualitative descriptive research was conducted in four stages: data collection and data checking, data reduction, data presentation and conclusions. The results showed that there were three types of absorption processes, namely adoption (as many as 51 vocabularies), adaptation (as many as 171 vocabularies) and adaptation adoption (as many as 47 vocabularies). There are five changes in meaning, namely changes in meaning narrowing (as many as 62 vocabularies), changes in meaning expanding (as many as 34 vocabularies), changes in total meaning (as many as 60 vocabularies), changes in meaning smooth (as many as 14 vocabularies), changes in meaning coarse (as many as 5 vocabularies). There are three types of borrowed meanings, namely full loanwords (86 words), partial loanwords (63 words), shift loanwords (26 words).